Turning 18 in specialised residential therapeutic care: Independence or a cliff edge?. (25th March 2021) - Field, Alice; Sen, Robin; Johnston, Claire; Ellis, Katie
Abstract: This article describes research undertaken in 2018 in a therapeutic residential home for young women with multiple and complex needs in out‐of‐home care in England. Based on qualitative interviews with five young women, aged 16–18, and four professionals working with the home, the article analyses the under‐researched leaving care needs and experiences of this group of young women. The findings highlight the tensions between notions of childhood and expectations of adulthood surrounding this group of young people. These converge around reaching the age of 18 and foreground vulnerability on the one side, and responsibility on the other.